Northrop Frye on Milton and Blake - Frye, Northrop (Frye, Northrop. Works. 1996, 2005)
The writings of John Milton and William Blake were central to Northrop Frye's concept of the imaginative structure of Western literature and thought. He considered them the two most important poet-prophets in the English tradition. This volume brings together all of Frye's writings on Milton and Blake from 1947 to 1987 - published and unpublished essays, reviews, commentaries, and public lectures - with the exception of Fearful Symmetry (published as Volume 14 of the Collected Works of Northrop Frye). During this time, Frye's engagement with Milton moved outward from the university into conferences, publications, and public lectures. His engagement with Blake, meanwhile, was a personal, intellectual, and spiritual quest, leading him to became the world authority on Blake in the mid-twentieth century. Angela Esterhammer, a student of Frye's in the 1980s, has provided annotation and an introduction that demonstrates the poets' importance for Frye's literary and cultural criticism and provides a twenty-first-century perspective on the legacy of his work. This key volume of the Collected Works will be important to scholars interested in Frye as well as those of Milton and Blake.